Role of the rootstock and its genetic background in plant mineral status assessed by petiole analysis and deficiency symptoms - Marine Morel; Sarah Jane Cookson; Jean-Pierre Da Costa; Nathalie Ollat; Elisa Marguerit (IVES Technical Reviews)
Rootstocks are potentially important levers of adaptation in the context of climate change. In this study, we investigated the effect of the rootstock and its genetic background on plant mineral status. The scion, the rootstock, and their interactions had a significant influence on petiole mineral content and explained the same proportion of phenotypic variance for most mineral elements. The rootstock effect was higher than the scion effect on the petiole concentration of a large majority of mineral elements. The joint evaluation of mineral status and deficiency symptoms highlights the diversity of rootstock-induced responses, and thus a new rootstock classification can be proposed to help growers optimise plant nutrition and fertiliser management.